2019
DOI: 10.1039/c9sc01427f
|View full text |Cite
|
Sign up to set email alerts
|

Isomeric triazines exhibit unique profiles of bioorthogonal reactivity

Abstract: Isomeric triazines can be tuned to exhibit unique reaction profiles with biocompatible strained alkenes and alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 54 publications
(76 reference statements)
1
40
0
Order By: Relevance
“…For example, 1,2,4‐triazine reacts with TCO with an adequate rate but not with NB or CYP [139] . Furthermore, 5‐ and 6‐substituted 1,2,4‐triazines (Figure 11c) and Tz have different reactivity profiles, [140] which opens up the possibility of running non‐interfering, i. e., orthogonal, cycloaddition reactions in parallel. For instance, the pair of 5‐substituted‐1,2,4‐triazine and thiacycloheptyne (TMTH in Figure 9a) could work together with the pair of Tz and CYP to achieve “orthogonal and bioorthogonal” conjugations [140] .…”
Section: Bioorthogonal Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 1,2,4‐triazine reacts with TCO with an adequate rate but not with NB or CYP [139] . Furthermore, 5‐ and 6‐substituted 1,2,4‐triazines (Figure 11c) and Tz have different reactivity profiles, [140] which opens up the possibility of running non‐interfering, i. e., orthogonal, cycloaddition reactions in parallel. For instance, the pair of 5‐substituted‐1,2,4‐triazine and thiacycloheptyne (TMTH in Figure 9a) could work together with the pair of Tz and CYP to achieve “orthogonal and bioorthogonal” conjugations [140] .…”
Section: Bioorthogonal Chemistrymentioning
confidence: 99%
“…Furthermore, 5‐ and 6‐substituted 1,2,4‐triazines (Figure 11c) and Tz have different reactivity profiles, [140] which opens up the possibility of running non‐interfering, i. e., orthogonal, cycloaddition reactions in parallel. For instance, the pair of 5‐substituted‐1,2,4‐triazine and thiacycloheptyne (TMTH in Figure 9a) could work together with the pair of Tz and CYP to achieve “orthogonal and bioorthogonal” conjugations [140] . Another diene with bioorthogonal potential is o ‐quinone (Figure 11c), which is produced via in situ oxidation (e. g., by using NaIO 4 ) of a catechol [141] .…”
Section: Bioorthogonal Chemistrymentioning
confidence: 99%
“…3 Cyclooctynes (CO), 16 norbornenes (NB), 20 and cyclopropenes (1,3-CP) 21,22 have been paired with tetrazines when a more stable dienophile is required, but these reactions are considerably slower (Scheme 2). Bulky dienophiles, such as 3,3-disubstituted cyclopropenes (3,3-CP) 23 and 3,3,6,6-tetramethylthiacycloheptynes (TMTH), 24 react poorly with tetrazines. These bulky dienophiles react with azides and allow for tandem labeling studies with tetrazine− trans -cyclooctene reactions for multitarget imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 1,2,4-triazines have been reported as potential bioorthogonal reagents offering excellent stability. [4][5][6][7][8][9][10][11] Unfortunately, 1,2,4-triazines react much slower in IEDDA reactions. Although it has been shown that the kinetics can be improved by the introduction of electronwithdrawing groups, 9,10 the rate constant is two-three orders of magnitude lower than for tetrazines.…”
mentioning
confidence: 99%
“…Additional motivation for the use of isomer 1 is that 5-substituted 1,2,4-triazines are the least sterically crowded and able to react even with sterically encumbered strained alkynes such as tetramethylthiacycloheptyne (TMTH). 5 To prepare the ligand 1, we first tested the most direct route by reacting 2-pyridineglyoxal 4 with formamidrazone 24 but unfortunately, the reaction gave a mixture of two isomers 1 and 3 that we could not separate either by recrystallization, or by column chromatography. We therefore used another synthetic route, depicted in Scheme 1.…”
mentioning
confidence: 99%